Reconstruction of legal protection for public institutions in the ITE Law after The Constitutional Court decision 105/PUU-XXII/2024 - Husni Mubarak; Aji Purnomo; Riswandha Imawan (Journal of Law, Administration, and Social Science, 2026)
The rapid expansion of digital communication has intensified public expression while simultaneously increasing the use of Article 27A of the ITE Law by state institutions to respond to public criticism, which culminated in Constitutional Court Decision Number 105/PUU-XXII/2024 that reinterpreted the phrase “other person” by excluding public institutions as victims of defamation, thereby generating significant debate regarding the balance between freedom of expression and the protection of state institutions Objective: This study aims to examine the legal status of public institutions after the Constitutional Court’s decision and to analyze the juridical implications of removing criminal protection within the framework of the principle of institutional protection in a constitutional democracy. Methodology: The research employs a normative legal approach using statutory and conceptual methods through the analysis of the Constitutional Court’s ruling, legal doctrines in criminal and constitutional law, and relevant scholarly literature on freedom of expression and institutional reputation. Findings: The results indicate that the concept of honor protected under defamation law is inherently personal and attached to individuals, not institutional entities, thus public institutions no longer possess legal standing as victims in criminal defamation cases, while institutional protection can still be pursued through civil remedies, rights of reply, and administrative clarification mechanisms. Implications: This study underscores that the removal of criminal protection for public institutions does not weaken state authority but instead strengthens democratic governance by preventing the criminalization of criticism, safeguarding freedom of expression, and promoting proportional, transparent, and rights-based mechanisms for protecting institutional credibility in the digital public sphere. Kata Kunci: Mahkamah Konstitusi, Perlindungan Hukum, Kebebasan Ekspresi.